2021
DOI: 10.1021/acscatal.0c04613
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Reaction Activity and Stability Benchmarks for Supported and Unsupported IrOx Electrocatalysts

Abstract: Advanced materials are needed to meet the requirements of devices designed for harvesting and storing renewable electricity. In particular, polymer electrolyte membrane water electrolyzers (PEMWEs) could benefit from a reduction in the size of the iridium oxide (IrOx) particles used to electrocatalyze the sluggish oxygen evolution reaction (OER). To verify the validity of this approach, we built a library of 18 supported and unsupported IrOx catalysts and established their stability number (S-number) values us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 47 publications
2
65
1
Order By: Relevance
“…Studies have shown that the dissolution can be alleviated by thermal annealing, despite the sacrifice of activity. [ 334 ] It is emphasized that electronic structure regulations and mechanism modulations help regulation of oxidation states [ 335 ] to avoid severe dissolution, which have been mentioned above. Moreover, the optimization of CL layer structure plays an important role in promoting mass transfer and maintaining stability.…”
Section: Application In Pemwementioning
confidence: 99%
“…Studies have shown that the dissolution can be alleviated by thermal annealing, despite the sacrifice of activity. [ 334 ] It is emphasized that electronic structure regulations and mechanism modulations help regulation of oxidation states [ 335 ] to avoid severe dissolution, which have been mentioned above. Moreover, the optimization of CL layer structure plays an important role in promoting mass transfer and maintaining stability.…”
Section: Application In Pemwementioning
confidence: 99%
“…However, due to the lack of conductivity, still relatively high iridium loadings are needed. 19 As potential alternative supports, tin oxide 20 and its doped analogues, such as antimony-doped tin oxide (ATO), 21 23 indium-doped tin oxide (ITO), 24 fluorine-doped tin oxide (FTO), 25 and tantalum-doped tin oxide (TaTO) 26 are often proposed; however, their use is still limited to the laboratory scale due to their stability constraints. 20 , 25 One of the potential supports is also doped titanium oxides.…”
Section: Introductionmentioning
confidence: 99%
“…[22] The interested reader is referred to a comprehensive review by Maillard and co-workers. [23] With the increasing production of renewable energy and concomitant depletion of fossil resources, the demand for efficient water splitting electrocatalysts continues to grow. Iridium (Ir) and iridium oxides (IrO x ) are currently the most promising candidates for an efficient oxygen evolution reaction (OER) in acidic medium, which remains the bottleneck in water electrolysis.…”
mentioning
confidence: 99%